2015
DOI: 10.1155/2015/615356
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Estrogen in Schizophrenia: Clinical and Preclinical Findings

Abstract: Gender differences in schizophrenia have been extensively researched and it is being increasingly accepted that gonadal steroids are strongly attributed to this phenomenon. Of the various hormones implicated, the estrogen hypothesis has been the most widely researched one and it postulates that estrogen exerts a protective effect by buffering females against the development and severity of the illness. In this review, we comprehensively analyse studies that have investigated the effects of estrogen, in particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(142 citation statements)
references
References 218 publications
3
119
0
12
Order By: Relevance
“…Nearly 50% of women with SZ have irregular menses that are frequently associated with low levels of estradiol, although this is not associated with neuropsychological status [Gleeson et al, 2016]. There is ample evidence of the protective effect of estradiol against SZ as it interacts with neurotransmitters, enhances cognition and memory, and reverses the symptoms [Gogos et al, 2015]. Male patients have, indeed, lower levels of testosterone than healthy controls, with an inverse correlation between serum testosterone and negative symptoms [Ramsey et al, 2013;Sisek-Šprem et al, 2015].…”
Section: Other Featuresmentioning
confidence: 99%
“…Nearly 50% of women with SZ have irregular menses that are frequently associated with low levels of estradiol, although this is not associated with neuropsychological status [Gleeson et al, 2016]. There is ample evidence of the protective effect of estradiol against SZ as it interacts with neurotransmitters, enhances cognition and memory, and reverses the symptoms [Gogos et al, 2015]. Male patients have, indeed, lower levels of testosterone than healthy controls, with an inverse correlation between serum testosterone and negative symptoms [Ramsey et al, 2013;Sisek-Šprem et al, 2015].…”
Section: Other Featuresmentioning
confidence: 99%
“…Recent clinical studies have demonstrated that adjunct treatment with 17βestradiol and estrogen-based compounds ameliorate positive, negative and cognitive symptoms experienced by patients diagnosed with schizophrenia or depression [29][30][31][32][33][34] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite these lines of evidence, the exact molecular and cellular mechanisms by which estrogens exert these beneficial effects are not well understood. The beneficial effects of 17β-estradiol in disorders such as SCZ and MDD have been proposed to occur through the modulation of monoamine transmitter systems such as dopamine and 5-HT, or via an anti-inflammatory mechanism 30,33,36,53 . However, increasing evidence suggests that the beneficial effects of 17β-estradiol may also be in part conferred through the modulation of glutamatergic signaling 27,35,36 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…127 Evidence comes from its interaction with the major neurotransmitter systems implicated in schizophrenia, animal research suggesting it may enhance cognition and reverse deficits reflective of the symptom and cognitive deficits of schizophrenia, and from clinical trials demonstrating additive effects when combined with antipsychotics. Its potential in PR samples is unknown.…”
Section: Characteristics and Correlates Of Psychosis Riskmentioning
confidence: 99%